Báo cáo Kết quả thực hành tiết kiệm, chống lãng phí trong năm 2022 (kèm báo cáo tóm tắt và các phụ lục). - Chính phủ (2023)
Toàn văn Báo cáo Kết quả thực hành tiết kiệm, chống lãng phí trong năm 2022 (kèm báo cáo tóm tắt và các phụ lục).